Semiconducting Carbon Nanotubes with Light‐Driven Gating Behaviors in Phototransistor Memory Utilizing an N‐Type Conjugated Polymer Sorting - Yi‐Hsuan Tung; Shang‐Wen Su; En‐Jia Su; Guo‐Hao Jiang; Chun‐Chi Chen; Sheng‐Sheng Yu; Chi‐Cheng Chiu; Chien‐Chung Shih; Yan‐Cheng Lin (Small Science, 2024)
Semiconducting single‐walled carbon nanotubes (s‐SWNTs) have arisen a growing interest in field‐effect transistors (FETs) due to their advantages, such as lower fabrication temperature, flexibility, and solution processing applicability, compared to traditional silicon‐based FETs. In this study, diversifying the functionality of s‐SWNT‐based FETs is focused on, particularly emphasizing their use in nonvolatile photomemory applications. By selectively wrapping s‐SWNT with n‐type conjugated polymers (CPs), electron‐trapping and photoresponsive capabilities are endowed in the device. After optimizing the structure and aggregating behavior of n‐type CPs, a favorable supramolecular network comprising s‐SWNT and CPs is formed and applied in phototransistor memory. Accordingly, the device exhibits a high memory ratio and window of 105 and 75.7 V, representing its remarkable charge‐storage capabilities. In addition, the device demonstrates decent long‐term stability over 104 s and multilevel memory behavior driven by the varied gate bias or accumulated light‐gating periods. The proposed memory mechanism involves electrical writing and photoerasing processes with the existence of n‐type CPs on s‐SWNT, revealing the underlying principles of charge transfer between their heterojunction interfaces. Herein, this research contributes to developing advanced phototransistor memory, offering a promising avenue for future electronic applications.